Development and Characterization of Tuna Peptide-Enriched Cookies - Parvathy, U; Jeyakumari, A; Prakasan, Sreepriya; Sreelakshmi, K R; Ninan, George (Fishery Technology, 2025)
Fish is a vital component of the human diet, offering a rich array of essential nutrients. Among the various species consumed, tuna stands out due to its high protein content. These proteins, when hydrolyzed into peptides, find wide-ranging applications in both the food and pharmaceutical industries due to their enhanced bioavailability and functional properties. The present study investigated fortification of cookies with fish-derived peptides obtained from tuna meat (Euthynnus affinis), hydrolyzed using papain to a degree of hydrolysis of 24.07%. Cookies were prepared in five formulations: a control (C0 ) and four peptide-enriched variants (C1 –C4 ), containing 0.431 g to 1.7 g of peptide-derived protein per cookie. Compared to the control, fortified cookies showed significant changes. The diameter of fortified cookies increased from 4.1 to 5.3 cm, while the weight decreased from 20 g to 17.8 g. The spread ratio reduced from 4.0 to 3.65 with increasing peptide levels. Hardness increased from 17.46 to 25.77 N, while the breaking force rose from 3.3 to 4.01 N. Sensory evaluation confirmed that all peptide-enriched cookies were acceptable, with no bitterness detected even at the highest peptide concentration. These findings highlight the potential of tuna-derived peptides as a functional ingredient in bakery products, offering enhanced nutritional and textural properties without compromising sensory appeal.